2001
DOI: 10.1097/00008506-200104000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Neuroscience Intensive Care Unit on Neurosurgical Patient Outcomes and Cost of Care

Abstract: Analysis of patient data from a new neuroscience intensive care unit (NSICU) permitted evaluation of whether such a specialty ICU favorably altered clinical outcomes in critically ill neuroscience patients, and whether such a care model produced an efficient use of resources. A retrospective review was performed to compare (1) the clinical outcomes, as defined by percent mortality and disposition at discharge, between patients with a primary diagnosis of intracerebral hemorrhage treated in 1995 in medical or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(142 citation statements)
references
References 26 publications
5
135
2
Order By: Relevance
“…4 Mirski et al also found that introducing a team to ICUs that is specifically trained for neuroscience critical care decreased mortality from 36% to 19% and increased the proportion of good outcomes in patients with intracranial hemorrhage from 48% to 69%. 5 Compared with these reports, our patients in both groups had much lower mortality rates (0.96%) and much improved neurological outcomes (complication rates were \ 5%). Taking into consideration that baseline outcomes were considerably improved in our patient population, it would be difficult to improve patient outcome without any interventions.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…4 Mirski et al also found that introducing a team to ICUs that is specifically trained for neuroscience critical care decreased mortality from 36% to 19% and increased the proportion of good outcomes in patients with intracranial hemorrhage from 48% to 69%. 5 Compared with these reports, our patients in both groups had much lower mortality rates (0.96%) and much improved neurological outcomes (complication rates were \ 5%). Taking into consideration that baseline outcomes were considerably improved in our patient population, it would be difficult to improve patient outcome without any interventions.…”
Section: Discussioncontrasting
confidence: 46%
“…2,3 In addition, it has been reported that utilization of a neurointensive care unit team decreased mortality rates, shortened hospital length of stay, and improved patient outcomes in the neurological and neurosurgical populations. 4,5 Collectively, it is conceivable that intensive care has a significant impact on critically ill patient outcomes. However, it has not been determined whether intensive care based on continuous monitoring (electrocardiogram (ECG), blood pressure, and pulse oximetry [SpO 2 ]) and frequent neurologic evaluation by ICU staff has a significant impact on elective neurosurgical patient outcome in those who are in good physical condition.…”
Section: Résumémentioning
confidence: 99%
“…We identified 12 studies, involving 24,520 patients, which presented original data comparing models of care for critically ill neurologic patients [3][4][5][6][7][8][9][10][11][12][13][14]. Four studies assessing subgroups derived from previously published data were excluded (see Electronic Supplementary Material) [15][16][17][18].…”
mentioning
confidence: 99%
“…This change has been fueled by the emergence of specialists who run and work in specialty units like the Neurocritical care unit (NCCU). These units have been shown to reduce morbidity, mortality, and the length of stay for critically ill neurologic patients [1][2][3]. The improved care in these units is driven by two underlying factors.…”
Section: Introductionmentioning
confidence: 99%
“…The improved care in these units is driven by two underlying factors. The availability of technological interventions that are performed in the context of neurological specialty units and the concentration of neurological patients in a single location were the judgment and experience of specialty providers results in better outcomes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%